2020
DOI: 10.18203/issn.2454-5929.ijohns20203203
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative mastoid cavity problems: a tertiary care centre experience

Abstract: <p class="abstract"><strong>Background:</strong> Aims and objectives of the study were to find incidence and causes for postoperative mastoid cavity problems after modified radical mastoidectomy.</p><p class="abstract"><strong>Methods:</strong> The present prospective study was conducted in the Department of ENT, SMGS Hospital, GMC Jammu from September 2017 to February 2020 on 25 patients with active squamosal chronic otitis media. All patients underwent modified radic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In one study by Rajan et al, 9 post-operative cavity complications were found in 26.92% patients. In study of Saraf et al, 10 total 25 patients underwent mastoidectomy, post-operative cavity problems were found in 36% patients and Sade et al 11 had 28% post mastoidectomy cavity problems and Kos et al 12 had 30% cavity problems. Khan et al 13 13 age range of the patients unresent mastoidectomy was 15-60 years and mean age was 29.8 ± 10.4.In one study by Saraf et al, 10 mean age of the patients was 29.4 years and most of the patients were 21-30 years.…”
Section: Discussionmentioning
confidence: 95%
“…In one study by Rajan et al, 9 post-operative cavity complications were found in 26.92% patients. In study of Saraf et al, 10 total 25 patients underwent mastoidectomy, post-operative cavity problems were found in 36% patients and Sade et al 11 had 28% post mastoidectomy cavity problems and Kos et al 12 had 30% cavity problems. Khan et al 13 13 age range of the patients unresent mastoidectomy was 15-60 years and mean age was 29.8 ± 10.4.In one study by Saraf et al, 10 mean age of the patients was 29.4 years and most of the patients were 21-30 years.…”
Section: Discussionmentioning
confidence: 95%
“…The accumulation of wax is among the most frequently encountered and complex postoperative problems for patients who undergo a canal wall down mastoidectomy. 13 A large, deep cavity with a small meatoplasty can cause problems for the debris to be cleaned out of the cavity. Patients have to have their mastoid cavities cleaned up routinely.…”
Section: Discussionmentioning
confidence: 99%